Insecticide Resistance Status of Malaria Vectors in a Malarious Area, Southeast of Iran - Jalil Nejati; Seyed Hassan Moosa-Kazemi; Mohammad Ali Oshaghi; Wrya Badzohre; Masoumeh Pirmohammadi; Zahra Saeidi; Nazanin Naseri-Karimi; Seyedeh Zahra Parkhideh; Hassan Vatandoost (Tehran University of Medical Sciences, 2022)
Background: Malaria continues to be the main vector-borne disease in Iran. The endemic foci of malaria are in Sistan and Baluchistan Province, the borderline of Iran and Pakistan. By the year 2020 the program of the country is malaria elimination. The main vector control is using insecti- cide as Indoor Residual Spraying. The aim of the study was to evaluate the susceptibility of main malaria vectors to different insecticides recommended by WHO. Methods: All the insecticides papers supported by WHO and evaluation of insecticide resis- tance of Anopheles stephensi, Anopheles culicifacies, Anopheles superpictus to different chemi- cal groups of imagicides including DDT 4%, malathion 5%, propoxur 01.%, lambdacyhalothrin 0.05%, deltamethrin 0.025% and permethrin 0.75% were followed by the WHO guideline. Results: Results of the susceptibility test against different insecticides revealed that An. stephensi and An. culicifacies are resistant to DDT and susceptible to other insecticides. An. superpictus is susceptible to all groups of pesticides. Conclusion: Knowledge on insecticide resistance in target species is a basic requirement to guide insecticide use in malaria control programmes in local and global scales.